Grain Sorghum Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; O'Brien, Daniel M.; Olson, Brian L.S. (My University, 2007)
This publication projects a budget that reflects expected income and costs based on typical production of grain sorghum in western Kansas.
MF904_2007_10
Keywords: MF904; Economics; Crops; MF